RFID adoption intention in retail sector in Malaysia / Soleyman Paydar - Paydar, Soleyman (Institute of Graduate Studies, UiTM, 2015)
Radio frequency identification (RFID) technology can be considered as an important application in retail operations and supply chain management (SCM) to increase the companies’ performance via tracking the real location information of products or equipment throughout the supply chain. Nevertheless, the expected rapid industry adoption of RFID has not taken place up to today as no supply chain organizations in Malaysia have adopted RFID yet. At the other side, Academic researches on RFID’s adoption in supply chain domain are still lacking. Regarding the control power of retailers in the supply chain, it is important to explore and investigate the basic drivers and obstacles in deciding to adopt RFID in the retail supply chain (RSC). Hence, this study aims to identify and evaluate a comprehensive set of factors that may influence RFID adoption intention in RSC in Malaysia and ascertain the inhibitors and facilitators of the adoption. To do this, an exploratory survey questionnaire was applied to collect data from 221 IT and Management Personnel in both Retailer and Hypermarket Sectors. This data was analyzed using the structural equation modelling technique. As the results, a comprehensive theoretical framework of IT innovation adoption in the supply chain and at inter-organizational level of analysis was proposed…